EXPERIMENTAL TAXONOMY OF THE GIGANTOCHLOA ATTER-GIGANTOCHLOA PSEUDOARUNDINACEA COMPLEX - Elizabeth A. widjaja; R.N. Lester (Research Center for Biology, 1987)
Gigantochloa pseudoarundinacea, G. robusta, G. atter, G. atroviola-cea and 14 other related Malesian species of bamboos were studied from preserved and living materials. Characters discerned by morphology, anatomy, chromatography and electrophoresis were analysed by numerical taxonomy. Most of the data indicated that the four species named above were distinct although closely related. The relationships of the remaining species were more complex, but the integrity of each species was established.